2019
DOI: 10.3390/cells8091042
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Fibrinogen-Like 1 as a Potential Biomarker for Radiation-Induced Liver Injury

Abstract: Liver damage upon exposure to ionizing radiation, whether accidental or because of therapy can contribute to liver dysfunction. Currently, radiation therapy is used for various cancers including hepatocellular carcinoma; however, the treatment dose is limited by poor liver tolerance to radiation. Furthermore, reliable biomarkers to predict liver damage and associated side-effects are unavailable. Here, we investigated fibrinogen-like 1 (FGL1)-expression in the liver and plasma after radiation exposure. We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…In addition, high plasma FGL1 expression is associated with poor response to immunotherapy, suggesting FGL1 as a potential biomarker for predicting the outcome of cancer immunotherapy [ 17 ]. Moreover, FGL1 expression had been reported to be upregulated both in vivo and in vitro following irradiation, indicating the possibility of FGL1 as a biomarker for liver injury [ 27 ]. In contrast, overall survival time was found to be remarkably shorter in patients with gastric cancer with high FGL1 expression than in gastric cancer patients showing low FGL1 expression [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, high plasma FGL1 expression is associated with poor response to immunotherapy, suggesting FGL1 as a potential biomarker for predicting the outcome of cancer immunotherapy [ 17 ]. Moreover, FGL1 expression had been reported to be upregulated both in vivo and in vitro following irradiation, indicating the possibility of FGL1 as a biomarker for liver injury [ 27 ]. In contrast, overall survival time was found to be remarkably shorter in patients with gastric cancer with high FGL1 expression than in gastric cancer patients showing low FGL1 expression [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Immunoblotting was performed as described previously [ 27 ]. Briefly, cells were lysed with RIPA buffer supplemented with protease inhibitor.…”
Section: Methodsmentioning
confidence: 99%
“…While a study showed that FGL1 promotes HCC tumor formation by inhibiting the activation of antigen-specific T cells 15 , another study found that FGL1 could inhibit the growth and proliferation of HCC, which runs counter to previous conclusions 19 . Therefore, the actual effect of FGL1 on hepatocytes is controversial 17 .…”
Section: Structure and Functionmentioning
confidence: 99%
“…FGL1 is inextricably linked to obesity 16 . Meanwhile recent researches have highlighted that FGL1 may be a dramatic and important benchmark for measuring radiation-induced liver damage 17 . FGL1 serves as a pivotal “bridge” between liver regeneration and adipose tissue function 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Trials in which therapies were tailored based on biomarker profiling indicated that matched therapy achieved a higher objective response rate and a lower toxicity [13,16,17]. From a clinical perspective, patients' circulating FGL1 may provide information on the activation status of the FGL1-LAG-3 pathway and serve as a diagnostic and prognostic biomarker in clinical studies to design and detect innovative immunotherapies [18][19][20]. In addition, the analysis of FGL1 in serum as a liquid biopsy is a simple and noninvasive alternative to surgical biopsies that allows doctors to gather a range of tumor-related information and provides clues to the most effective immunotherapy.…”
Section: Introductionmentioning
confidence: 99%